Cultural distance perceived by Chinese audiences in the Korean film Silenced: a study of cross-cultural receptions in film content elements - Gao, Xiaotian; Hamedi, Mohd Adnan; Wang, Changsong (Frontiers in Communication, 2024)
In the realm of cross-cultural film dissemination, cultural distance emerges as a pivotal factor influencing the reception of domestic audiences to foreign cinematic productions. Despite Korea's thriving film industry and China's vast film market, the cultural distance experienced by Korean films in China remains largely unexplored. This study focuses on the Korean film Silenced, renowned as a classic that champions justice in Korea. By employing qualitative survey and thematic analysis, this study investigates the cultural distance perceived by forty-four Chinese audiences when watching Silenced. The findings revealed that various content elements, such as the film's setting, translation of verbal expression, nonverbal expression of film characters, and visuals/non-diegetic music did not exhibit cultural distance among Chinese audiences. Nevertheless, the plots of morally compromised characters with positive identities, theme exploration of societal darkness and human darkness, and tragic ending introduced a palpable sense of cultural distance perceived by Chinese audiences. This study scrutinizes the outcomes through the lenses of Korean film and Chinese audiences. While certain aspects of Korean cinema and Chinese audience preferences exhibit cultural proximity, mitigating barriers to appreciation in select content domains, Silenced adeptly employs the plots, themes, and ending to delve into the darkness of human nature and societal dynamics. However, under the influence of China's official propaganda and film censorship, Chinese participants evinced a constrained appreciation for cinematic portrayals of human and societal darkness. Concurrently, Chinese participants manifested expectations for films to provide a source of relaxation, a notion incongruent with the oppressive ambiance evoked by Silenced.